Characterization of tropical rainfall structure for some selected locations in Nigeria (2021)
Rainfall rate for any location is required for rain attenuation modeling for the region of interest. The characteristics of tropical rainfall structure in Nigeria have been investigated. The data was collected from the Tropical Data Acquisition network (TRODAN) set up by the Center for Atmospheric Research (CAR) in Nigeria. The rainfall rates were measured at 5-minutes integration time. The results were then compared with those predicted by the ITU-R model, and those from other tropical locations. The results revealed that the ITU-R model performs best only in the Southern Guinea Savannah (SGS) region of the country. In other geographical locations, the ITU-R model either under-estimates or over-estimates rainfall rates. The Cumulative Distribution Functions (CDFs) at the 0.01% time of exceedence showed that the percentage difference in the measured rain rate and the ITU-R estimates varied from a minimum of 4.89% in SGS to a maximum of 22.93% in the Derived Savannah (DS). At the 0.001% of time, these differences varied from a minimum of 11.90% to a maximum of 38.80% in these respective regions. These results and others from the tropics suggest the need for the modification of the ITU-R model for predicting rain attenuation in the tropical region to take into account the peculiar characteristics of rainfall in the region.